Business data communications - Agrawal, Manish 1969- (Hoboken, NJ Wiley, 2011)
"Unlike other books in the field, Business Data Communications provides IT specialists with a very focused approach that shows how the concepts are relevant to their work. Unique content is presented on topics ranging from multiplexing, signaling, CRC, and CIDR to supporting technologies, subnetting, and 802.11n and 802.16. Numerous lab exercises are integrated throughout the pages to demonstrate how the material is applied. It also includes a companion Web site that enhances each chapter with relevant, easy-to-read research articles that IT specialists will appreciate"--Provided by publisher.
Machine generated contents note: -- Chapter 1: Introduction and layering -- This is the introductory chapter. It makes the case for why computer networks are important, how networks evolved to their current state, why data is sent as packets, why packets are organized in layers. It then introduces the TCP/ IP stack, the OSI model and the functions of each layer. -- Professional implications -- Business implications of networks -- Technology milestones -- Packetization -- Layering -- TCP/ IP model -- OSI model -- Principles of Internet protocols -- Chapter 2: Physical layer -- This chapter introduces the need for physical media and signals, describes the important properties of common media and signals, provides an example of converting from data to signal, and shows an example of multiplexing. -- Functions of the physical layer -- Physical media and their properties -- Signals and their properties -- Multiplexing -- Importance of binary signals -- Binary counting -- Signal representation of data -- Chapter 3: Data Link Layer -- This chapter describes the working of Ethernet, structure of Ethernet frames and MAC addresses. The need of CRC for error correcting is described, along with an example of CRC computation and verification. The role of switches is also introduced. -- Ethernet overview -- CSMA/ CD -- Error detection and correction -- Ethernet frame structure -- Switches -- Chapter 4: Network Layer -- This is one of the central chapters. It describes IP addresses in detail, the need for CIDR, procedures for obtaining IP addresses, calculating subnet masks. This chapter also deals with converting between binary and decimal numbers to facilitate working with the dotted decimal notation. -- Functions of network layer -- Internet protocol (IP) -- IP Header -- IP Addresses -- Binary numbers -- CIDR notation -- Chapter 5: Transport Layer -- This chapter motivates the need for segmentation and reassembly. It then describes the primary TCP functions including flow control, reliability. Port addressing is covered in detail. UDP is also introduced. -- Need for TCP -- TCP functions -- Segmentation -- Reliability -- Flow-control -- Multiplexing -- Connection establishment -- TCP Header -- UDP -- Chapter 6: Applications -- This is a long chapter which introduces the most frequently encountered network application protocols. The section on the web (HTTP) focuses heavily on business applications of the web including search and search advertising. Estimates of the size of the global Internet are made. The section on email introduces students to SMTP, POP and IMAP protocols and also includes some good practices on using email. -- Overview of the application layer -- Overview of the Web -- Overview of E-mail -- Overview of FTP -- Overview of SSH -- Overview of IM -- Chapter 7: Support services -- This chapter aggregates the important supporting technologies that enable the Internet to function effectively. At this point in the course, students are expected to feel comfortable with the basic packet transmission mechanism and be ready to discuss "value-add" features such as DHCP and DNS. The section on DHCP introduces the need for dynamic address allocation and introduces address leasing. NAT begins with the motivation for the technology which introduces complexity into the network. The section on DNS is quite detailed with an introduction to the hierarchical structure of DNS, top level domains such as .us and .org, address lookups. Since students now have all the information necessary to understand how a typical home network works, the chapter ends with an overview of home networking. -- DHCP -- Network address translation -- Address resolution protocol -- Domain Name System -- Home networking -- Chapter 8: Subnetting -- This chapter introduces the need for subnetting and the procedures to calculate subnet masks. -- Chapter 9: Routing -- The section on routing introduces terms such as autonomous systems, displays some sample routing table entries to help students visualize how routers work, the bgplay applet is used to give students a peek into the dynamic structure of the Internet. -- Routing -- Route aggregation -- Chapter 10: WAN technologies -- This chapter introduces the important carrier technologies. It begins with an introduction to virtual circuits and describes the salient features of important carrier grade technologies -- Virtual circuits -- T carriers -- Frame relay -- ATM -- MPLS -- Chapter 11: Wireless networks -- This chapter describes wireless LAN technologies. Conceptually, this chapter would be integrated with chapter 3, which deals with the data link layer. Practically however, it is useful to keep chapter 3 simple with a focus on error detection and correction in a relatively benign wired environment. This chapter can then compare wireless LANs with wired LANs. All the popular wireless LAN technologies - wi-fi, Bluetooth and WiMAX are introduced in this chapter. -- Business role of wireless LANS (WLANs) -- ISM frequency bands -- 802.11a/b/g/n - Wi-Fi -- 802.15 - Bluetooth Personal area networks -- 802.16 - WiMax -- Chapter 12: Telephony and cell phones -- This chapter covers the basic principles of the telephone network and the distinctions between telephone networks and computer networks. The evolution of cell phone networks from 1G to 3G is also described -- Circuit switching -- Telephone network operation -- Cell phone networks - 1G - 3G -- CDMA -- Chapter 13: Network security -- This chapter introduces network security. It provides a summary of key incidents such as the TJ Maxx and Sweetbay cases to highlight the important of securing the IT infrastructure against attacks originating from the network. It organizes security controls into two categorizes - protecting data from malicious hackers outside the organization and securing information when it is sent to legitimate users outside the organization. -- Common security concerns -- Definition -- Inbound security -- Firewalls -- DMZs -- Authentication and authorization -- Patching -- Outbound security -- Encryption, including TLS, WEP, WPA -- Chapter 14: Standards and legal issues -- This is the conclusion chapter. It introduces standards, legal, social, political and other non-technical issues that are important for the success of networks.
Keywords: Business enterprises -- Computer networks; Computer networks; Data transmission systems; Information technology -- Management